The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1021/jp963928f
|View full text |Cite
|
Sign up to set email alerts
|

Calculations and Characterization of the Electronic Spectra of DNA Bases Based on ab Initio MP2 Geometries of Different Tautomeric Forms

Abstract: The absorption spectra and transition moment directions of the four DNA bases and uracil were calculated, utilizing the semiempirical INDO/S-CI method and the ab initio CIS/6-31G* method. A linear scaling of the CIS/6-31G* transition energies was necessary to get good agreement with the observed energies. CASPT2 π → π* transition energies and polarizations of adenine were also calculated. Fully MP2/6-31G*-optimized geometries were used in the calculations of the electronic spectra. The effect of possible taut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 45 publications
10
133
2
Order By: Relevance
“…Table I shows the computed wavelengths and oscillator strengths for the lowest energy vertical transitions of the single-stranded (three base) and doubled-stranded (six base) structures studied. As the method used, CIS, is known to systematically over-estimate transition energies, mainly due to its neglect of electron correlation, the computed energies have been scaled by a constant factor of 0.72, as recommended by Broo and Holmén [9]. It should be noted that the absolute values of the oscillator strengths will also be lower than those predicted by the CIS method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Table I shows the computed wavelengths and oscillator strengths for the lowest energy vertical transitions of the single-stranded (three base) and doubled-stranded (six base) structures studied. As the method used, CIS, is known to systematically over-estimate transition energies, mainly due to its neglect of electron correlation, the computed energies have been scaled by a constant factor of 0.72, as recommended by Broo and Holmén [9]. It should be noted that the absolute values of the oscillator strengths will also be lower than those predicted by the CIS method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As a rule, excitation energies are substantially overestimated in the CIS calculations, since it fails to properly account for differences in dynamical electron correlation in the ground and the excited states. Broo and Holmén have suggested that this difference is comparable in all the nucleobases and have used a scaling factor of 0.72 for the excitation energies of π − π * transitions [22].…”
Section: Transition Characteristicsmentioning
confidence: 99%
“…Guanine has been the subject of many theoretical [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and experimental investigations. [30][31][32][33][34][35][36][37][38] Over the years a wealth of information about its ground and electronically electronic states has been gathered.…”
Section: Introductionmentioning
confidence: 99%